Single nucleotide polymorphisms predisposing to asthma in children of Mauritian Indian and Chinese Han ethnicity - Ramphul, K. (Associação Brasileira de Divulgação Científica, 2014)
Our objective was to investigate the distributions of six single nucleotide polymorphisms (SNPs) MS4A2 E237G, MS4A2 C-109T, ADRB2 R16G, IL4RA I75V, IL4 C-590T, and IL13 C1923T in Mauritian Indian and Chinese Han children with asthma. This case-control association study enrolled 382 unrelated Mauritian Indian children, 193 with asthma and 189 healthy controls, and 384 unrelated Chinese Han children, 192 with asthma and 192 healthy controls. The SNP loci were genotyped using polymerase chain reaction (PCR)-restriction fragment length polymorphism for the Chinese Han samples and TaqMan real-time quantitative PCR for the Mauritian Indian samples. In the Mauritian Indian children, there was a significant difference in the distribution of IL13 C1923T between the asthma and control groups (P=0.033). The frequency of IL13 C1923T T/T in the Mauritian Indian asthma group was significantly higher than in the control group [odds ratio (OR)=2.119, 95% confidence interval=1.048-4.285]. The Chinese Han children with asthma had significantly higher frequencies of MS4A2 C-109T T/T (OR=1.961, P=0.001) and ADRB2 R16G A/A (OR=2.575, P=0.000) than the control group. The IL13 C1923T locus predisposed to asthma in Mauritian Indian children, which represents an ethnic difference from the Chinese Han population. The MS4A2 C-109T T/T and ADRB2 R16G A/A genotypes were associated with asthma in the Chinese Han children.